(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2013)
The filtration coefficient of dry grounds of the aeration zone of investigated territory has been determined on the data of experimental pouring in wells. The received data can be used during working out measures of decrease ground waters’ level and their removal, necessary for reconstruction of the underground, as well as for making various filtration calculations, connected with the projecting and construction of different engineering constructions in the zone of aeration.